IMPLICATION OF LIQUIDITY RATIO ON EFFECTIVE TAX RATE WITH GROWTH TAX RATE AS AN INTERVENING VARIABLE - Lenny Lenny; Nasib P. Manurung; Beatrix Delina (International Journal Labs, 2024)
The worldwide economy was halted by COVID-19, which had an enormous influence on the property and real estate industries. Due to those circumstances, many property and real estate organizations were unable to pay all of their maturing debts on time because they lacked the present assets to meet their commitments. Thirteen hypotheses are included in this quantitative-associative research. The growth tax rate is positively impacted by the quick ratio. Both the quick ratio and the growth tax rate have a positive impact on the effective tax rate. However, the growth tax rate is not impacted by the current, cash and cash turnover ratio. The ratios of current, cash, and cash turnover have impact on the effective tax rate. While the growth tax rate has an impact on the effective tax rate through the quick and cash turnover ratio, The current and cash ratios, however, have no bearing